2009
DOI: 10.1182/blood-2008-11-191148
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic T cells induce ceramide-rich platforms in target cell membranes to initiate graft-versus-host disease

Abstract: Alloreactive donor cytolytic T lymphocytes play a critical role in pathophysiology of acute graft-versus-host disease (GVHD). As GVHD progression involves tumor necrosis factor superfamily receptor activation, and as apoptotic signaling for some tumor necrosis factor superfamily receptors might involve acid sphingomyelinase (ASMase)-mediated ceramide generation, we hypothesized that ASMase deletion would ameliorate GVHD. Using clinically relevant mouse models of acute GVHD in which allogeneic bone mar-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Thus presence of BMDCs at the site of CR might be explained by direct influx of BMDCs from intracranial vessels that have lost their BBB integrity. Previous data has reported that lymphocytes are recruited to the site of RT injury and can attach to vessel EC and infiltrate into normal brain parenchyma [27], [28]. We examined this possibility by staining for possible peripheral blood cells such as erythrocytes, granulocytes, megakaryocytes, Natural Killer cells, T and B cells using immunohistochemistry and immunofluorescence analysis in addition to 2PLM imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Thus presence of BMDCs at the site of CR might be explained by direct influx of BMDCs from intracranial vessels that have lost their BBB integrity. Previous data has reported that lymphocytes are recruited to the site of RT injury and can attach to vessel EC and infiltrate into normal brain parenchyma [27], [28]. We examined this possibility by staining for possible peripheral blood cells such as erythrocytes, granulocytes, megakaryocytes, Natural Killer cells, T and B cells using immunohistochemistry and immunofluorescence analysis in addition to 2PLM imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicate that ceramides play important roles in inflammatory processes, and it has been shown that host acid SMase are imperative for maximal GVHD-associated pathology (10). In the aforementioned study, lack of host acid SMase reduced the acute inflammatory phase of GVHD, attenuating the cytokine storm (10). In the inflammatory disease cystic fibrosis, ceramides induce the upregulation of proinflammatory mediators, albeit via an unknown mechanism (11).…”
Section: Introductionmentioning
confidence: 94%
“…Using clinically‐relevant mouse models of acute GVHD in which allogeneic bone marrow and T cells were transplanted into wild‐type and asmase −/− hosts, the authors identified host ASMase as critical for full blown GVHD. More specifically, the mechanism by which ASMase mediates CTL‐induced apoptosis of target cells (hepatocytes, small and large intestinal epithelium and endothelium, skin) appeared to require CRP formation on target cell membranes [132]. The lack of host ASMase, and in turn abrogation of CRP formation (defined using an ex vivo 2 cell model of GVHD in which in vivo‐activated T cell effector cells were coincubated with asmase +/+ or asmase −/− hepatocyte target cells), attenuated organ injury and consequent cytokine storm, decreasing morbidity and mortality.…”
Section: Manipulation Of Crps In Disease Treatmentmentioning
confidence: 99%